Redeeming Ulos Batak through Christian Religious Education and its Implications - Roedy Silitonga; Dirk Roy Kolibu (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
Ulos is a local cultural product of the Batak community worn during every traditional ceremony. However, since the preaching of the Christian Gospel in the late 18th century in Tapanuli, North Sumatra, Indonesia, the presence of Christianity has grown rapidly and influenced the social and cultural life of the Batak people, especially in the use of ulos. Initially, the use of ulos was not considered problematic, but later, with the arrival of various Christian denominations that had different beliefs from what was taught in the church before, conflicts arose. The purpose of this research is to examine how the use of ulos has caused conflicts with Christianity. This article uses a qualitative approach with descriptive analysis and synthesis of thoughts on the relationship between Christianity and culture. The instruments used for analysis and synthesis include literature studies, observations, and interviews with Batak cultural figures. The main findings are as follows: first, positioning ulos as a traditional weaving that can be used as a unique form of local wisdom; second, using ulos within the framework of building socio-cultural relations for the Batak people and other ethnic groups; third, creating and using ulos as an example of teaching material for the redemption of local culture in a contemporary context. The analysis and synthesis results recommended by the author regarding the use of ulos as one of the teaching materials in the Christian Religious Education curriculum for the cultivation of local wisdom values for church congregants and students in schools.